1978
DOI: 10.1029/ja083ia06p02453
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal effects in E region low‐latitude nitric oxide

Abstract: Measurements of nitric oxide in the lower E region made by the ultraviolet nitric oxide experiment on Atmosphere Explorer C during 1974 are used to demonstrate diurnal and seasonal effects at low latitudes. At the equator, NO increases by about a factor of 2 between sunrise and the early afternoon; this is followed by a small decline toward sunset. Seasonally, NO shows an asymmetry about the equator with more NO on the summer side than on the winter side; at equinox the asymmetry vanishes. These effects are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Current results suggest an increase by a factor of about 2 from winter to summer, at latitudes of 25°-40°near solar minimum (e.g. Stewart and Cravens, 1978;Ge´rard and Noe¨l, 1986). This is sufficient to make appreciable changes to the E-region ionisation.…”
Section: The Production and Loss Of Nomentioning
confidence: 95%
“…Current results suggest an increase by a factor of about 2 from winter to summer, at latitudes of 25°-40°near solar minimum (e.g. Stewart and Cravens, 1978;Ge´rard and Noe¨l, 1986). This is sufficient to make appreciable changes to the E-region ionisation.…”
Section: The Production and Loss Of Nomentioning
confidence: 95%
“…Both individual NO profiles and zonally and time-averaged latitude/altitude distributions were presented. Future experimental studies should combine the latitude (or magnetic latitude) and longitude coverage of the 105-km AE-C studies Stewart and Cravens, 1978] with the altitude coverage of this AE-D study. That is, threedimensional data sets should be constructed and analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This relation was convolved with the instrumental sensitivity function in order to give a curve of growth function between the instrumental counts recorded during an integration period and the slant column density of NO. Stewart and Cravens [1978] presented this function for the UVNO spectrometer on the AE-C satellite. The function for the AE-D instrument is virtually identical to the AE-C one if the AE-C function is multiplied by a factor of 1.83.…”
Section: Measurements and Data Analysismentioning
confidence: 99%
“…The spectrometer data were acquired during the daylight hours. Stewart & Cravens (1978) have found that [NO] tends to decrease, by a factor of up to 2, between sunset and sunrise. Sternberg and Ingham (1982) carried out a seminal programme of observations on the night sky continuum over the 4100-8200 A range from the Haute-Provence Observatory for a period of several years near sunspot maximum.…”
Section: Rocket Investigationsmentioning
confidence: 99%